2007
DOI: 10.1063/1.2719007
|View full text |Cite
|
Sign up to set email alerts
|

Electrically detected and conventional magnetic resonance investigation of surface and bulk states in polyaniline thin films

Abstract: Electrically detected magnetic resonance ͑EDMR͒ and electron paramagnetic resonance ͑EPR͒ were used to investigate emeraldine base polyaniline films. The magnetic susceptibility presented a Curie ͑localized spins͒-Pauli ͑delocalized spins͒ transition at 240 K, when we also observed a transition in the dependence of the g factor with temperature ͑T͒. Peak-to-peak linewidth decreases with increasing temperature, reflecting that motional narrowing limits the hyperfine and dipolar broadening in this polymer. EDMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Experiments to support this theory are in progress. Nevertheless, the observed effects of increased mechanical stiffness of the PEG/PANI composite in magnetic field is well within the range predicted by (8) and supported by experimental measurement shown in Figure 43.…”
Section: Appendix a Clarification On Effect Of Magnetic Field On Stif...supporting
confidence: 87%
See 1 more Smart Citation
“…Experiments to support this theory are in progress. Nevertheless, the observed effects of increased mechanical stiffness of the PEG/PANI composite in magnetic field is well within the range predicted by (8) and supported by experimental measurement shown in Figure 43.…”
Section: Appendix a Clarification On Effect Of Magnetic Field On Stif...supporting
confidence: 87%
“…Polyaniline is a conducting polymer in its emeraldine state. Recent studies [8,13,25,29] on the polyaniline emeraldine have shown it to be paramagnetic material. Studies on the doped polyaniline emeraldine salt compared to undoped polyaniline emeraldine base form of the polymer also revealed increased magnetic susceptibility due to doping [25].…”
Section: A1 Magnetic Properties Of Polyanilinementioning
confidence: 99%
“…Experiments to support this theory are in progress. Nevertheless, the observed effects of increased mechanical stiffness of the PEG/PANI composite in magnetic field is well within the range predicted by (8) and supported by experimental measurement shown in Figure 43.…”
Section: Appendix a Clarification On Effect Of Magnetic Field On Stif...supporting
confidence: 87%
“…Polyaniline is a conducting polymer in its emeraldine state. Recent studies [8,13,25,29] on the polyaniline emeraldine have shown it to be paramagnetic material. Studies on the doped polyaniline emeraldine salt compared to undoped polyaniline emeraldine base form of the polymer also revealed increased magnetic susceptibility due to doping [25].…”
Section: A1 Magnetic Properties Of Polyanilinementioning
confidence: 99%
“…[140] Hyperfine field effects have long been considered to be important in the physics of organic semiconductors and molecular electronic reactions in general. [89,[141][142][143][144][145][146][147][148] Possibly the most remarkable manifestation of the effect of hyperfine fields in electron-transfer reactions is found in the mechanism governing the migration ability of birds. Some avian species incorporate highly magnetic field-dependent ocular sensory elements, which provide visual guidance with respect to the Earth's magnetic field.…”
Section: From the Hyperfine Field To Coherent Spin Beatingmentioning
confidence: 99%